Mechanical characterization of waste-rubber-modified recycled-aggregate concrete. (15th June 2016) - Li, Li-Juan; Tu, Gui-Rong; Lan, Cheng; Liu, Feng
Abstract: A waste-rubber-modified recycled-aggregate concrete (RMRAC) intended for road construction was produced by adding granulated waste rubber to recycled-aggregate concrete (RAC). The impact mechanical properties of the RMRAC were studied using a variable cross-section 74-mm-diameter split-Hopkinson pressure bar (SHPB). The dynamic mechanical properties and the toughness of the RMRAC were studied at four strain rates, corresponding to four different input pressures, and were compared to those observed in the static condition. The effects of the rubber particle size, rubber content, and strain rate on the dynamic compressive strength and toughness of the RMRAC were analysed. Test results show that the RMRAC exhibits an enhanced strain rate effect and has good impact resistance relative to RAC.